Predictive value of tissue cagA status in Helicobacter pylori infection - Murat SARUÇ; M. Akif DEMİR and Nurten KÜÇÜKMETİN and Feyzullah GÜÇLÜ and Sabriye ÖZKAYA and Ali Rıza KANDİLOĞLU and Ulus Salih AKARCA and Hakan YÜCEYAR (Turkish Journal of Gastroenterology, 2019)
-